NEONTOLOGICAL ASSESSMENT OF RISK TO PUBLIC HEALTH FROM EMISSIONS OF HYDROCARBONS FROM THE RESERVOIR MODEL GAS STATION - Антропченко, А.К.; Бойченко, С.В.; Радомская, М.М.; Черняк, Л.М. (Science-based technologies, 2015)
The network of filling stations makes a contribution to the formation of urban pollution and climate change. The activities of filling stations poses a serious risk to human health, you must evaluate it and determine possible means of prevention of negative consequences of influence of these man-made objects. The article presents calculations neontological risk to public health from exposure to oil vapor formed as a result of operation of fuel tanks at gas stations. Simulation results are presented in graphical form and predicted time of occurrence of adverse changes in the human body that are in the impact zone. The results of the risk assessment neontological show that the level of danger of evaporation of gasoline varies from acceptable to very high. This result is associated with an increase in the intensity of evaporation of petroleum products by increasing the temperature depending on the summer and winter periods